Reduction of interlayer coupling in NiFeCo/Cu/NiFeCo/FeMn spin valve structures by lowering argon sputtering pressure - Park, CM; Shin, KH (AMER INST PHYSICS, 1997)
Sputtered spin valve heterostructures of NiFeCo/Cu/NiFeCo/FeMn were prepared to examine the effect of the argon sputtering pressure on the interlayer coupling between two ferromagnetic layers, The coupling strength was found to be closely related to the argon sputtering pressure. As the argon sputtering pressure is varied from 6 to 1 mTorr; the coupling field is reduced from 13.6 to 0.5 Oe. In particular, the sample deposited at 1 mTorr exhibits a coupling field of 0.5 Oe and a resistance change of 1.7% for the field step of 0.1 Oe leading to a sensitivity as large as 17% Oe. The reduced interlayer coupling is attributed to the modified topography of NiFeCo/Cu/NiFeCo interfaces, Atomic force microscope analyses support the dominant role of a topography-related effect in reducing the interlayer coupling strength. (C) 1997 American Institute of Physics.
Keywords: GIANT MAGNETORESISTANCE; UNIDIRECTIONAL ANISOTROPY; MULTILAYERS